Herding cats : a "Sarah's scribbles" collection - Andersen, Sarah (Sarah C.) (A Sarahs scirbbles collection, 2018)
“With characteristic wit and charm, Sarah Andersens third collection of comics and illustrated personal essays offers a survival guide for frantic modern life: from the importance of avoiding morning people, to Internet troll defense 101, to the not-so-life-changing futility of tidying up. But when all else fails and the world around you is collapsing, make a hot chocolate, count the days until Halloween, and snuggle up next to your furry beacon of hope”Back cover.